Beberapa Faktor Yang Berperan Terhadap Purchase Intention Produk - Yosan Pratama Rachmandanu; Aulia Danibrata (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
Overall, the purpose of this research was to determine the effect of brand awareness, brand association, perceived quality, and brand loyalty on purchase intention of Smartphones in Bekasi. The research design used descriptive research and causality research. The sampling method used in this study was purposive sampling and as many as 120 data were obtained from respondents who were in Bekasi. Primary data was used in this research and the data was collected by distributing questionnaires to respondents. The method of analysis used multiple regression equation model. The final results of this research showed that brand association, perceived quality, and brand loyalty have an influence on purchase intention, and on the other side brand awareness does not affect purchase intention.